1985
DOI: 10.1002/cne.902360402
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of somatostatin‐like immunoreactivity in the monkey hippocampal formation

Abstract: The distribution of somatostatin-like immunoreactivity was studied in the hippocampal formation of the Old World (Macaca fascicularis) and New World (Saimiri sciureus) monkeys. Series of coronal sections were processed by the unlabeled second antiserum method using primary antisera which recognize somatostatin-28 (S309) or somatostatin-28(1-12) (S320). Neuronal cell bodies were more readily stained with antiserum S309 and were observed throughout the hippocampal formation. The most prominent accumulations of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
41
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 47 publications
10
41
0
Order By: Relevance
“…The presence of somatostatin-like immunoreactivity has been reported in several monkey brain regions, including prefrontal, temporal and occipital cortex, neocortex and the hippocampal formation (Bakst et al 1985;Lewis et al 1986;Campbell et al 1987;De Lima and Morrison 1989). There was a reasonably good correlation between SR1F levels in neurons and/or fibers reported by these authors and [125I]LTT-SR1F-28 labelling found in this study.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of somatostatin-like immunoreactivity has been reported in several monkey brain regions, including prefrontal, temporal and occipital cortex, neocortex and the hippocampal formation (Bakst et al 1985;Lewis et al 1986;Campbell et al 1987;De Lima and Morrison 1989). There was a reasonably good correlation between SR1F levels in neurons and/or fibers reported by these authors and [125I]LTT-SR1F-28 labelling found in this study.…”
Section: Discussionsupporting
confidence: 76%
“…Sloviter and Nilaver (1987) and LkrBnth et al (1990) reported a rare few SOM+ cells resembling pyramidal basket cells in the rat. A sirnilar finding has been reported by Bakst et al (1985) in the macaque monkey. Some VIP+ cells resemble pyramidal (Kiihler, 1983) and ML basket cells (Swanson ct al., 1987).…”
Section: Non-principal Cellsmentioning
confidence: 77%
“…Thus we have reason to believe that the pattern of immunoreactivity in fact represents the distribution of parvalbumin-containing fibers and terminals. The preferred termination of PARV-immunoreactive terminals within or close to the cell layers suggests that the somatostatin-containing subgroup of nonpyramidal cells, which in the fascia dentata terminates in the outer molecular layer (Bakst et al 1985;Milner and Bacon 1989;Leranth et al J 989), does not contain PARV. This is in line with a recent report by Kosaka et al (1988) suggesting that parvalbumin and somatostatin rarely co-exist in the same nonpyramidal cell.…”
Section: P a R V-containing Cell Typesmentioning
confidence: 94%